Yuga-yugoṃ meṃ Kāśī - Verma, Thakur Prasad, 1933-; Siṃha, Devī Prasāda, 1947-; Miśra, Jayaśaṅkara, 1939- (Bharatiya Itihas Sankalan Samiti publication, 1986)
Papers presented at National Seminar on "Kashi Through the Ages" held in Varanasi in August 1985.